Friendship in relation to self-esteem and academic achievment of children in grade V at Miag-ao Central Elementary school. - Gerial, Shiela Eva
This sought to examine the relationship of friendship to self-eteem and academic achievements of a child. The study hypothesized that: 1) There is adirect relationship between friendship and self-esteem; 2) There is a direct relationship between self-esteem and academic achievements. (p)Sixty (60) Grades V pupils were participated in the study. They were officially enrolled in the academic year of 2000-2001 at Miagao Central Elementary School. Friendship was measured by Furman's Friend Relationship Questionnaire. It was originally composed of 51-item scale but the researchers decided to include only the warmth/closeness factors. Self-concept was measured by the used of the Piers-Harris Self-concept Scale, which composed of 80 declarative statements, answerable by Yes and No. Pearson ProductMoment Correlation (r) was utilized to anlyze the data and to determine whether there were a direct relationship between the variables. The result of the study revealed that there was no direct relationship between friendship and self-esteem.